Analisis Karakteristik Klinis dan Efektifitas Terapi Antiplatelet pada Pasien Stroke berulang di Rumah Sakit X - Raising, Rahmawati; Hermawatiningsih, Oktaviarika Dewi (Parapemikir : Jurnal Ilmiah Farmasi, 2025)
Recurrent ischemic stroke poses a significant challenge in clinical practice due to its association with high rates of disability and mortality. Antiplatelet therapy serves as the cornerstone of secondary stroke prevention, yet its effectiveness is influenced by patients' clinical characteristics. This study aimed to analyze the relationship between clinical characteristics and the effectiveness of antiplatelet therapy in recurrent stroke patients at Hospital X. Methode A retrospective observational study with a case-control design was conducted. Data were collected from medical records of patients meeting inclusion criteria and analyzed descriptively and inferentially using the Kolmogorov-Smirnov normality test and Chi-Square test. Results showed that the majority of recurrent stroke patients were female (64%), with the dominant age group being 46–65 years (63%), and 66% had a history of non-hemorrhagic stroke. The longest mean time to recurrent stroke was observed in patients receiving a combination of aspirin and clopidogrel (410.54 days), followed by aspirin monotherapy (359.95 days) and clopidogrel monotherapy (330.82 days). However, these differences were not statistically significant (p = 1.000). Conclusion, recurrent stroke patients exhibited high-risk profiles characterized by female predominance, middle-aged to elderly demographics, and a high prevalence of ischemic stroke and hypertension history. While combination antiplatelet therapy (aspirin-clopidogrel) showed numerically longer recurrence-free intervals compared to monotherapies, no statistically significant difference was found among the three treatment groups.